Teaching and Learning Languages with ChatGPT: Challenges and Opportunities in Multilingual Classrooms in Higher Education - Hyunjoo Moon; Yesung Chung; Adah Ward Randolph (IJELTAL (Indonesian Journal of English Language Teaching and Applied Linguistics), 2025)
While there is a growing body of research on the role of ChatGPT in English language teaching and learning, its application in diverse language education remains underexplored. This study addresses this gap by examining how language instructors of non-English languages integrate ChatGPT into their teaching practices. Adopting a phenomenological case study approach, we explored the lived experiences and perceptions of 13 language instructors at a Midwestern U.S. university. Participants were purposefully selected based on three criteria: (1) they taught their native language as a second or foreign language in higher education; (2) they attended a workshop on ChatGPT facilitated by the research team; and (3) they were non-native English speakers who had used ChatGPT for their own English learning. Data were collected through semi-structured interviews conducted one month after the workshop. Interviews were recorded, transcribed, and thematically analyzed following Braun and Clarke’s (2006) six-step process. The analysis revealed how participants used ChatGPT to support language instruction and learning, the perceived benefits and challenges of ChatGPT in multilingual contexts, and evolving teacher roles in the era of AI. Findings underscore the need to expand ChatGPT’s multilingual capabilities and support educators in integrating AI responsibly and effectively. This study contributes practical insights into how AI tools can complement human instruction in diverse language classrooms and inform institutional support and policy development for AI integration in higher education.